E-Sakip Sebagai Media Peningkatan Kinerja Aparatur Pemerintah Kabupaten Sleman Tahun 2020 - Kelibay, Ismed; Kadir, Muhammad Arifin Abd; Salmah, Ummu; Nurjannah, Siti (Universitas Muhammadiyah Sorong, 2025)
The research conducted provides an in-depth examination of the implementation of E-SAKIP as a medium to improve the performance of government apparatus in Sleman Regency in delivering electronic-based public services in 2020. The method used is qualitative research. Data sources come from the E-SAKIP platform of the Sleman Regency Government, as well as relevant journal articles. The data were analyzed using Nvivo 12 Plus. The research findings show that in 2020, the performance of the Sleman Regency government apparatus in providing public services improved significantly thanks to the implementation of E-SAKIP. Despite the COVID-19 pandemic, the services delivered to the public were carried out optimally. Based on these findings, it is concluded that the presence of E-SAKIP has had a positive impact on improving the performance of government personnel, public programs, and activities, as well as budget absorption in line with targets. To provide simpler, faster, more effective, and efficient services, E-SAKIP enables services to be accessed electronically—easily, quickly, anytime, anywhere, and under any circumstances.